The Maternal Diet, Gut Bacteria, and Bacterial Metabolites during Pregnancy Influence Offspring Asthma - Gray, Lawrence E. K.; O’Hely, Martin; Ranganathan, Sarath; Sly, Peter David; Vuillermin, Peter (Frontiers in Immunology, 2017)
This review focuses on the current evidence that maternal dietary and gut bacterial exposures during pregnancy influence the developing foetal immune system and subsequent offspring asthma. Part 1 addresses exposure to a farm environment, antibiotics, prebiotic and probiotic supplementation that together indicate the importance of bacterial experience in immune programming and offspring asthma. Part 2 outlines proposed mechanisms to explain these associations including bacterial exposure of the fetoplacental unit; immunoglobulin related transplacental transport of gut bacterial components; cytokine signalling producing fetomaternal immune alignment; and immune programming via metabolites produced by gut bacteria. Part 3 focuses on the interplay between diet, gut bacteria and bacterial metabolites. Maternal diet influences faecal bacterial composition, with dietary microbiota accessible carbohydrates (MACs) selecting short chain fatty acid (SCFA) producing bacteria. Current evidence from mouse models indicates an association between increased maternal dietary MACs, SCFA exposure during pregnancy and reduced offspring asthma that is, at least in part, mediated by the induction of regulatory T lymphocytes (Tregs) in the foetal lung. Part 4 discusses considerations for future studies investigating maternal diet-by-microbiome determinants of offspring asthma including the challenge of measuring dietary MAC intake; limitations of the existing measures of the gut microbiome composition and metabolic activity; measures of SCFA exposure; and the complexities of childhood respiratory health assessment.